PROTOTIPE KANTIN TANPA UANG BERBASIS KARTU PINTAR - Paulus Insap Santosa (JUTI: Jurnal Ilmiah Teknologi Informasi, 2010)
This paper presents a desktop application prototype that uses smart cards for payment mode without cash transaction at a canteen. Smart cards, used for authentication, are also designed to have information of cash balance and some personal data of card holders. Application developed is still a prototype that has not connected into the banking system to refill the balance into the smart card. This prototype is a desktop application. Features that have been successfully developed and run well in these applications include food settings, user settings, and reports sales per period.